2020
DOI: 10.1038/s41598-020-73221-x
|View full text |Cite
|
Sign up to set email alerts
|

Rajyoga meditation induces grey matter volume changes in regions that process reward and happiness

Abstract: Studies provide evidence that practicing meditation enhances neural plasticity in reward processing areas of brain. No studies till date, provide evidence of such changes in Rajyoga meditation (RM) practitioners. The present study aimed to identify grey matter volume (GMV) changes in reward processing areas of brain and its association with happiness scores in RM practitioners compared to non-meditators. Structural MRI of selected participants matched for age, gender and handedness (n = 40/group) were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 85 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…Intriguingly, the larger grey matter volume, evidenced from magnetic resonance imaging, in long-term mediators is linked to the improved cognitive, emotional, and attention control [ 174 ]. Mounting evidence shed light on the benefits of different yoga and meditation techniques on the cognition, emotional balance, attention control, reward, and happiness which is correlated to increased grey matter volume [ 174 , 175 , 176 , 177 , 178 ]. Indeed, the loss of dendritic spines is positively correlated to decrease in grey matter volume in stressful conditions in mice [ 179 ].…”
Section: Non-therapeutic Modulators Of Dendritic Spinesmentioning
confidence: 99%
“…Intriguingly, the larger grey matter volume, evidenced from magnetic resonance imaging, in long-term mediators is linked to the improved cognitive, emotional, and attention control [ 174 ]. Mounting evidence shed light on the benefits of different yoga and meditation techniques on the cognition, emotional balance, attention control, reward, and happiness which is correlated to increased grey matter volume [ 174 , 175 , 176 , 177 , 178 ]. Indeed, the loss of dendritic spines is positively correlated to decrease in grey matter volume in stressful conditions in mice [ 179 ].…”
Section: Non-therapeutic Modulators Of Dendritic Spinesmentioning
confidence: 99%
“…In healthy population raja yoga meditators were found to have greater positivity and happiness than matched controls [28] . A recent study has also shown grey matter volume changes in happiness related areas in raja yoga meditators [2] . However, if the same will hold true (Brahma Kumaris Raja yoga meditation as a preventive tool) in the context of uncertainties like the COVID 19 pandemic needs to be further studied in controlled trials.…”
Section: Discussion and Future Recommendationsmentioning
confidence: 83%
“…As one of the cortical executive regions, the aPFC plays an essential role in pain appraisal [45]. Structurally, previous studies reported that chronic pain led to gray matter loss [46][47][48][49], whereas meditation increased gray matter volume in the aPFC region [50]. Functionally, studies have found greater aPFC activation with meditation practice [51].…”
Section: Principal Findingsmentioning
confidence: 99%